Readmission of Stroke Patients and Risk Factors: Literature Review - Laely, Anna Jumatul; Nursalam, Nursalam; Efendi, Ferry (Indonesian Journal of Global Health Research, 2024)
Stroke is still a concern for the health consent due to its high mortality and morbidity rates. Readmission of stroke patients is one of the factors that causes it. Risk factors that causing readmission of stroke patients are the main focus for nurses in order to give nursing services to patients in hospital. The aim of the research is to describe the evidence base for factors that cause readmission in stroke patients. This study is a literature review,with approach using 10 journals. Articles that were reviewed were selected from Google Scholar, Ebsco, Clinical key and Proquest which had been peer-reviewed and published. The inclusion criteria in the search were full-text articles, original text, English language, and the last 5 years, while the keywords used in the search for articles were caused factor, readmission, and stroke patient. The results of the data search obtained 539 articles, 10 articles were then reviewed. The articles used cross-sectional design (n=5) and cohort study (n=5), the cohort design consists of 3 retrospective studies, 2 prospective cohort studies. The causal factors related to the incidence of readmission in stroke patients are unpreventable factor and preventable factor of readmission. Unpreventable factors related to basic demographic data (age, gender, ethnicity, residences) and type of stroke. Meanwhile, preventable factors related to infection, complication of comorbid and the patient's functional ability during discharge. Readmissions of stroke patients are an indicator of services quality provided to patients during their hospitalization. Provision of services according to standards, prevention of infection and complications from patient are the main things that can reduce patient readmission rates.